The TTG-Amphibolite Terrains of Arctic Fennoscandia: Infinite Networks of Amphibolite Metatexite-Diatexite Transitions - Halla, Jaana (Frontiers in Earth Science, 2020)
In the Archaean, the Earth’s early basaltic crust episodically converted into felsic TTG (tonalite-trondhjemite-granodiorite) crust by unknown tectonic processes. To contribute to the debate on the possible tectonic settings of TTGs, this paper illustrates and explains migmatite structures of TTG-amphibolite terrains in Arctic Fennoscandia. The Lake Inari and Rommaeno complexes in northern Finland and West Troms Complex in northern Norway consist of folded and banded TTG gneisses with abundant amphibolite enclaves. The terrains show migmatite structures generated by in-situ and in-source melting of amphibolites and repeated metatexite-diatexite transitions that form infinite and boundless interconnected networks over vast areas. The aim of this paper is to show that the TTGs of these terrains represent coalesced in-situ and in-source neosomes of amphibolite protoliths and are not similar to granitoids sensu stricto generated by modern-style plate tectonics. The best-fit explanation for the origin of the TTG-amphibolite associations of Arctic Fennoscandia is intracrustal differentiation by in-situ and in-source partial melting of metabasalts in deep parts of a thick oceanic plateau. Preliminary geochemical results on bimodal TTG-amphibolite sample sets of the Lake Inari Complex as well as some other recent TTG research support this conclusion. Successful further research on the formation of the Earth’s earliest crust requires a three-fold strategy of parallel investigations of TTGs and associated basalts as well as migmatite structures.